2021
DOI: 10.1186/s12936-021-03741-y
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and prevention practices on malaria among the indigenous Orang Asli community in Kelantan, Peninsular Malaysia

Abstract: Background Malaysia is on track towards malaria elimination. However, several cases of malaria still occur in the country. Contributing factors and communal aspects have noteworthy effects on any malaria elimination activities. Thus, assessing the community’s knowledge, attitudes and practices (KAP) towards malaria is essential. This study was performed to evaluate KAP regarding malaria among the indigenous people (i.e. Orang Asli) in Peninsular Malaysia. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Beliefs concerning P. knowlesi malaria etiology influenced their attitude, self-efficacy, and ways of coping with antimalarial measures [ 40 ]. A proportion of the community in Indonesia had local supernatural beliefs towards malaria [ 40 ], and this perception was also present among the Orang Asli community in neighboring country, Malaysia [ 50 ]. This signals a gap in disease prevention as communities have different perspectives and beliefs towards malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Beliefs concerning P. knowlesi malaria etiology influenced their attitude, self-efficacy, and ways of coping with antimalarial measures [ 40 ]. A proportion of the community in Indonesia had local supernatural beliefs towards malaria [ 40 ], and this perception was also present among the Orang Asli community in neighboring country, Malaysia [ 50 ]. This signals a gap in disease prevention as communities have different perspectives and beliefs towards malaria.…”
Section: Discussionmentioning
confidence: 99%
“…The Malaysian government launched the National Malaria Elimination Strategic Plan 2011-2020 with the final goal of the complete elimination of locally-acquired malaria (excluding P. knowlesi) in Peninsular Malaysia by 2015 and in East Malaysia by 2020 [10]. The national strategic malaria elimination plan currently outlines seven key actions to achieve the elimination goal, including strengthening malaria surveillance system through an online system, intensifying control activities by indoor residual spray (IRS) and insecticide-treated nets (ITN), ensuring early case investigation, prompt treatment and outbreak management as well as improving community awareness and knowledge of malaria [32]. These concerted efforts have resulted in a significant reduction in overall malaria incidence, particularly P. vivax cases, over the last decade in Malaysia.…”
Section: Discussionmentioning
confidence: 99%
“…Located approximately 40km from Gua Musang town, the typical climate of the study area is tropical monsoon with temperature ranged between 20°C to 32°C and average annual rainfall between 2,000 mm to 4,000 mm. While the main economic activity was centred on agriculture such as palm oil plantation, the livelihood of the villagers mainly depended on rubber-tapping, labourers, farmers and gathering and selling forest products 23 . Previous studies have shown that this locality experienced high intestinal parasitic infections 24,25 as well as recurrent malaria outbreaks, which possibly related to autochthonous outbreaks of vivax malaria in the neighbouring state 20 .…”
Section: Study Area and Populationmentioning
confidence: 99%
“…A community-based cross-sectional survey was carried out between June and July 2019 23 . All indigenous Temiar Orang Asli of both sexes, residing in the study villages and aged one and older were invited to take part in the study.…”
Section: Study Design and Sampling Techniquesmentioning
confidence: 99%
See 1 more Smart Citation